Konsep Kecerdasan Buatan (Artificial Intelligence) Dalam Manajemen Kurikulum SD / MI - Yenni Fitriani; Supratman Zakir; Ramadhoni Aulia Gusli; Kurnia Mira Lestari (Jurnal Publikasi Ilmu Manajemen, 2024)
Entering the era of Industrial Revolution 4.0 and the current era of Society 5.0, requires schools to upgrade and evolve so that they can produce great Human Resources and be ready to face this increasingly advanced era. A primary school education is important to prepare for this. Elementary school curriculum management must be planned and developed following the very rapid developments of the times and seeing student development. The curriculum leads to the course of the learning process in order to measure student learning outcomes. Artificial Intelligence is artificial intelligence technology to help humans survive, so it needs to be applied in the world of education as preparation for students to recognize and utilize technology in everyday life. Using the Narrative Literature Review method, this article describes the concept of curriculum management in artificial intelligence-based elementary schools through studying four relevant literature. In learning, Artificial Intelligence technology can act as a Tutor System, Intelligent Tutor, learning tools/media, and a guide for creating curriculum and education policies. The results of this research provide an overview of the concept of an Artificial Intelligence-based elementary school curriculum, so that it can serve as a guideline in SD/MI curriculum management activities.